A macroscopic model for magnetorheological elastomers based on microscopic simulations. (1st June 2020) - Kalina, Karl A.; Metsch, Philipp; Brummund, Jörg; Kästner, Markus
Abstract: In this contribution, we present a novel proceeding for the development of a suitable macroscopic model for magneto-active composites. Based on a general continuum formulation of the coupled magneto-mechanical boundary value problem, valid for finite strains, a microscopic modeling approach is applied within a computational homogenization scheme. The calculated effective magneto-mechanical response of the composite system is used to identify the parameters of the macroscopic model. The merit of this strategy is the identification of the model fitting parameters independent of any macroscopic sample geometry. Furthermore, it facilitates the generation of large databases consisting of multiple load cases without performing expensive experiments. This strategy is applied for several microstructures with random particle distributions, where two-dimensional plane strain problems in the linear magnetization regime are considered for now. Finally, the magnetostrictive behavior of a macroscopic magneto-rheological elastomer sample is simulated for different sample geometries and underlying microstructures.